MULTIPLE ZIRCON GROWTH DURING FAST EXHUMATION OF DIAMONDIFEROUS, DEEPLY SUBDUCTED CONTINENTAL CRUST (KOKCHETAV MASSIF, KAZAKHSTAN) - Hermann J.; Rubatto D.; Korsakov A.; Shatsky V.S. (My University, 2001)
Diamondiferous rocks from the Kokchetav Massif, Kazakhstan, represent deeply subducted continental crust. In order to constrain the age of ultra high pressure (UHP) metamorphism and subsequent retrogression during exhumation, zircons from diamondiferous gneisses and metacarbonates have been investigated by a combined petrological and isotopic study. Four different zircon domains were distinguished on the basis of transmitted light microscopy, cathodoluminescence, trace element contents and mineral inclusions. Mineral inclusions and trace element characteristics of the zircon domains permit us to relate zircon growth to metamorphic conditions. Domain 1 consists of rounded cores and lacks evidence of UHP metamorphism. Domain 2 contains diamond, coesite, omphacite and titanian phengite inclusions providing evidence that it formed at UHP metamorphic conditions (P>43 kbar; T~950 C). Domain 3 is characterised by low-pressure mineral inclusions such as garnet, biotite and plagioclase, which are common minerals in the granulite-facies overprint of the gneisses (P~10 kbar; T~800 C). This multi-stage zircon growth during cooling and exhumation of the diamondiferous rocks can be best explained by zircon growth from Zr-saturated partial melts present in the gneisses. Domain 4 forms idiomorphic overgrowths and the rare earth element pattern indicates that it formed without coexisting garnet, most probably at amphibolite-facies conditions (P~5 kbar; T~600 C). The metamorphic zircon domains were dated by SHRIMP ion microprobe and yielded ages of 527±5, 528±8 and 526±5 Ma for domains 2, 3 and 4 respectively. These indistinguishable ages provide evidence for a fast exhumation beyond the resolution of SHRIMP dating. The mean age of all zircons formed between UHP metamorphic conditions and granulite-facies metamorphism is 528ǅ Ma, indicating that decompression took place in less than 6 Ma. Hence, the deeply subducted continental crust was exhumed from mantle depth to the base of the crust at rates higher than 1.8 cm/year. We propose a two-stage exhumation model to explain the obtained P-T-t path. Fast exhumation on top of the subducted slab from depth >140 to ~35 km was driven by buoyancy and facilitated by the presence of partial melts. A period of near isobaric cooling was followed by a second decompression event probably related to extension in a late stage of continental collision.